Perencanaan Panel Listrik Lift di PT Tiga Kreasi Indonesia - Hijroh Tamamil Gina; Mustofa Abi Hamid (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The main purpose of this study is to investigate in depth regarding the planning of electrical panels to be used in elevator systems. The method used is a literature study followed by the creation of panels and data collection. This process starts from the initial stage, namely making drawings of the electrical panel series, then continues with construction planning and installation of the overall elevator system. Selain itu, pengecekan berkala terhadap kualitas lift yang dipasang juga menjadi fokus utama dalam penelitian ini. This is important to ensure that elevators operating in these tall buildings can maintain safety and comfort when used by people and in the process of transporting goods to various floors of the building. Thus, it is hoped that the results of this study can make a meaningful contribution in improving the efficiency and safety of vertical transportation within modern high-rise buildings.